Sisters of the Sari - Baker, Brenda L. (New York : NAL Accent, 2011)
While vacationing in India, a driven CEO of a major corporation becomes obsessed with the idea of building decent housing for the country's poor working women after befriending a former slave and current maid who lives in a homeless shelter.
Lariat Reading List, TLA 2012
Keywords: Women executives -- Fiction; Americans -- India -- Fiction; Female friendship -- Fiction; Self-realization in women -- Fiction